2021
DOI: 10.1177/23094990211045219
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between talofibular impingement and increased talar tilt in incongruent varus ankle osteoarthritis

Abstract: Purpose This study aimed to evaluate the relationship between talofibular impingement and increased talar tilt in incongruent varus ankle osteoarthritis. Methods: Incongruent varus ankle osteoarthritis was defined as a talar tilt of more than 4° on standard ankle anteroposterior radiographs. We retrospectively reviewed 30 patients with unilateral incongruent varus ankle osteoarthritis with normal alignment of the contralateral ankle. All patients underwent bilateral weightbearing computed tomography and stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…In the present study, the ankle alignment was also evaluated radiologically to screen for signs of osteoarthritis. Contrary to Tallroth's study, the mean TT was physiologic in both groups [33]. Nevertheless, measurements of the TT indicated that in valgus patients, the TT was oriented in valgus and in varus patients, and the TT was oriented in varus.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In the present study, the ankle alignment was also evaluated radiologically to screen for signs of osteoarthritis. Contrary to Tallroth's study, the mean TT was physiologic in both groups [33]. Nevertheless, measurements of the TT indicated that in valgus patients, the TT was oriented in valgus and in varus patients, and the TT was oriented in varus.…”
Section: Discussioncontrasting
confidence: 94%
“…And in the varus group, the TT was oriented in varus (Table 2). Albeit the TT was significantly different between both groups, it was not pathological for neither of one of the groups [33]. Correlation analysis revealed that the TT significantly correlated with the mTFA (Pearson's cor = 0.32, p < 0.006) indicating that higher grades of valgus at the knee joint were associated with higher grades of valgus malalignment at the ankle joint and vice versa (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, the midfoot lacks a typical movement pattern during a gait cycle in our sample likely because it is supposed to be stable in healthy individuals during walking, especially in the frontal and transverse planes. The midfoot is worth tracking clinically since reduced or increased mobility of the midfoot during walking can suggest pathological gait when compared to healthy controls [3, 19, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Although both stages 3a and 3b of arthritis are included in stage 3 of the modified Takakura's classification, their pathological characteristics and prognosis after joint preserving procedures, including supramalleolar osteotomy (SMO) and calcaneal osteotomy, are significantly different. [5][6][7] SMO is a representative joint preserving procedure, and this procedure is commonly performed with or without a fibular osteotomy (FO). SMO is effective in correcting the load axis of varus deformity and the articular surface at the distal ankle joint.…”
mentioning
confidence: 99%
“…Several previous studies have reported good results in SMO without FO, [11][12][13] however, some studies have even reported good clinical results in SMO with FO. 4,5 Although several studies have reported the effectiveness of additional FO in SMO, they could not clearly establish the clinically necessary and definite indication of FO in performing SMO. Although, as a biomechanical method, some previous studies have conducted cadaveric studies, 14,15 the pathological characteristics of VAA may not be accurately reflected on cadavers, such as a quantitative tilting angle grade in the talotibial joint interface and amount of talus translation.…”
mentioning
confidence: 99%